The Narrated Memory: A Fascination Stretched Out Over Past, Present, and Future (KULT_online, 2017)
Since the dawn of men memories have been of great interest. By drawing on literary and philosophical works, especially from the last century, the philosophical monograph Sein Leben Schreiben attempts to make the ways of memories observable. Emil Angehrn explores memories in their existential meaning and their interaction with the concept of life-writing and human temporal experiences. His considerations are highly worth reading and a thoroughly well written reflection on the entanglement between memories, time, language, and the self. Moreover, he raises the question why we desire memories in the first place.